INSTALLATION FOR RESEARCH OF THE ENERGY SPECTRUM OF COSMIC RAYS - Burtebayev, N.T.; Oskomov, V.V.; Saduev, N.O.; Kalikulov, O.A. (Recent Contributions to Physics, 2011)
The qualitative picture of a special case, formation elektron-photon and muon components is investigated at passage of primary cosmic rays through terrestrial atmosphere and one of methods of their registration at height of 850 m above sea level.